Cyclical helping hands: seasonal tailwinds differentially affect migrating Oriental Storks (Ciconia boyciana) travel speed - Shujuan Fan; Qingshan Zhao; Hongbin Li; Baoguang Zhu; Shubin Dong; Yanbo Xie; Lei Cao; Anthony David Fox (Avian Research, 2020)
Abstract Background The Oriental Stork (Ciconia boyciana) breeds in southeastern Siberia and parts of northeast China, and winters mainly in southeast China. Although the autumn migration pattern of Oriental Storks has been previously described, differences between spring and autumn migration travel speed in relation to wind assistance were unknown. Methods Using GPS/GSM transmitters, we tracked the full migrations of 18 Oriental Storks during 2015‒2018 to compare differences in autumn and spring migration patterns, and combined the satellite telemetry data with the National Center for Environmental Prediction Reanalysis data to explain the relationship between 850 mbar wind vectors and seasonal differences in travel speed. Results Differences in tailwinds contributed to significant differences in daily average Oriental Storks travel speed in spring (258.11 ± 64.8 km/day) compared to autumn (172.23 ± 49.7 km/day, p < 0.001). Storks stopped significantly more often in autumn than spring (1.78 ± 1.1 versus 1.06 ± 0.9, p < 0.05), but stopover duration (15.52 ± 12.4 versus 16.30 ± 15.1 days, respectively, p = 0.3) did not differ significantly. Tailwinds at 850 mbar pressure level (extracted from the National Center of Environmental Prediction Reanalysis data archive) significantly affected daily flying speed during spring and autumn migration. Tailwind conditions in spring (mean 4.40 ± 5.6 m/s) were always more favourable than in autumn when they received no net benefit (0.48 ± 5.6 m/s, p < 0.001). Despite mean spring migration duration being less than autumn (27.52 ± 15.9 versus 32.77 ± 13.4 days, p = 0.17), large individual variation meant that this duration did not differ significantly from each other. Conclusions For long distance migratory soaring birds (such as storks), relative duration of spring and autumn migration likely relates to the interaction between imperative for earliest arrival to breeding grounds and seasonal meteorological conditions experienced en route.